Dal materialismo storico alla filosofia della praxis - Vacca, Giuseppe (International Gramsci Journal, 2023)
Contrary to what the first editors and interpreters of Gramsci maintained, the expression “philosophy of praxis” is not a simple expedient to which he had recourse in order to avoid writing “historical materialism” and, thereby, to get round the prison censorship. The term, instead, implies a thoroughgoing rethinking of Marxism on his part which took place throughout the course of his reflections in the Notebooks, a rethink which has roots in the 1926 essay on the Southern Question. As well as taking up again the thought of Labriola (in whom the expression “philosophy of praxis” already figures), this “revision” of Marxist philosophy implies not only a definitive detachment from Marxism-Leninism, but an “epistemological break” with his own previous political writings and, above all, a new reading of Marx’s work, with particular attention paid to the Theses on Feuerbach and to the Preface to A Contribution to the Critique of Political Economy. Additionally, this also taking place in relation to the deep upheavals in the international political scenario between the end of the 1920s and the 1930s, which saw the definitive closure of the perspective of a world proletarian revolution. This led Gramsci to go in depth into the concepts of hegemony, the intellectuals, the State, civil society, war of position, passive revolution, and structure and superstructure, in an absolutely original reflection whose endpoint is the constitution of a new political subject in the modern world, namely the political party.